Discrepancy, involvement, and attitude change - Gavino, Jasmin A. ([Metro Manila] Psychological Association of the Philippines, 1971)
To test contradicting predictions of two theories of attitude change (Festinger's cognitive dissonance theory and Hovland, Harvey, and Sherif's assimilation-contrast theory) the level of discrepancy in an expirement similar to Zimbardo's was extended to the most objectionable level. A before and after design was used in which 24 pairs of sweethearts (Group 1- girls and boys and 27 pairs of best friends (Group 2- all girls) gave their opinions on the locus of blame in a case study. After respons involvement was manipulated Ss were exposed to what was allegedly the opinion of their sweetheart (Group 1) or their best friend (Group 2). A 2x3 analysis if variance was performed separately for the two groups on a composite change index. Results indicated that for both groups the discrepancy factor was significant. The point of maximum opinion change for the two group was within the latitude of rejection contrary to the predictions of Hovland, Harvey and Sherif.
Includes bibliographical references (page 8)
Keywords: Psychology Philippines -- Periodicals